Analysis of the capacity of Salmonella enterica Typhimurium to infect the human Placenta. (August 2019) - Perry, Ian D.; Nguyen, Tina; Sherina, Valeriia; Love, Tanzy M.T.; Miller, Richard K.; Krishnan, Lakshmi; Murphy, Shawn P.
Abstract: Introduction: Salmonella species are gram-negative facultative intracellular bacteria that are common causes of foodborne illness in North America. Infections by Salmonella during pregnancy are a significant cause of fetal loss in domestic livestock, and fetal and maternal mortality in mice. Furthermore, Salmonella infection is associated with miscarriage, stillbirth and preterm birth in pregnant women. Despite these collective associations, the extent to which S almonella can infect the human placenta has not been investigated. Methods: Human placental villous explants from several gestational ages were exposed to S almonella enterica serovar Typhimurium (STm) ex vivo . Infection was assessed by colony forming unit assay and whole mount immunofluorescence (WMIF). Results: Viable bacteria were recovered from placental villous explants of all gestational ages tested, but the bacterial burden was highest in 1st trimester explants. Bacterial numbers did not change appreciably with time post-infection in explants from any gestational age examined, suggesting that STm does not proliferate in placental villi. Exposure of villous explants to STm strains defective for the type III secretion systems revealed that Salmonella pathogenicity island 1 is essential for optimal invasion. In contrast to placental explants, STm infected and proliferated within villous cytotrophoblast cells isolated from term placentas. WMIF demonstrated that STm was restricted primarily to the syncytiotrophoblast layer in infected placentas. Discussion: Our study demonstrates that STm can invade into the syncytiotrophoblast but does not subsequently proliferate. Thus, the syncytiotrophoblast may function as a barrier to STm infection of the fetus. Highlights: STm can infect human placental explants from multiple gestational ages. STm does not proliferate within human villous tissue at any gestational age. STm infects and proliferates within isolated term villous cytotrophoblast cells. STm infection was restricted to the syncytiotrophoblast (SYN) layer. The SYN may function as a barrier to STm infection of the fetus.